2014
DOI: 10.3109/02713683.2013.853194
|View full text |Cite
|
Sign up to set email alerts
|

Type I Collagen Accelerates the Spreading of Lens Epithelial Cells through the Expression and Activation of Matrix Metalloproteinases

Abstract: Type I collagen promotes the expression and activation of MMPs in a LEC-specific manner. These results suggest that type I collagen may play a role in PCO development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The normal lens capsule is mainly composed of laminin (LM) and type IV collagen [1719]. Type I collagen is not detected in the capsule of normal lenses [20]. However, Type I collagen is expressed in cataractous lenses [21,22], and increases with age in human lens capsules [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal lens capsule is mainly composed of laminin (LM) and type IV collagen [1719]. Type I collagen is not detected in the capsule of normal lenses [20]. However, Type I collagen is expressed in cataractous lenses [21,22], and increases with age in human lens capsules [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous LM peptides were able to induce MMP-9 expression [45,46]. LECs cultured on type I collagen-coated dishes exhibited high expression levels of the pro-form of MMP-9 [20]. However, there is currently no evidence that shows a potential role of MMP-9 in senescent LECs or in senescent lens capsules of ARC.…”
Section: Introductionmentioning
confidence: 99%
“…Elschnig pearls and Soemmering ring) [27]. Furthermore, it can accelerate fibrosis by direct interaction with lens epithelial cells through metallo-matrix proteinases in lens epithelial cells [28]. This might explain why its presence is higher in the capsular folds, where fibrosis is increased.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first study to evaluate the concentration of MMP-2 in the aqueous humor of dogs with cataracts. The decision to investigate MMP-2 was based on previous studies that reported that the latent form of such gelatinase was found to be the most relevant MMP in normal eyes of humans, rabbits, dogs, and chicken (Di Girolamo et al 1996, Weinstein et al 2007, Shimada et al 2014. Although slightly increased concentrations of MMP-2 were observed in dogs with mature cataracts than in controls, significantly higher values were only detected in patients with the hypermature stage of this affection.…”
Section: Discussionmentioning
confidence: 99%